A Review of the Application of the Nearly Zero Energy Building Concept in Different Climates - Akbar, Fajril; Nazir, Refdinal; Ampuh Hadiguna, Rika (LPPM Universitas Andalas, 2023)
The building sector consumes about 30% of the world's primary energy demand. Conventionally, reducing building energy consumption is done through energy saving or energy conservation activities. Nearly zero energy building (nZEB) itself can be defined as a provision that implies a value of energy consumption that is as low as possible or an energy-efficient building, then determines the energy source that is able to meet these energy needs. These strategies can generally be done with passive design, active design, and comprehensive energy management approaches [6]. This article presents an overview of the implementation of nZEB and finds out the shortcomings in terms of strategies and techniques used for different types of buildings and climates. Given the differences in climate and building characteristics, we found that each region has different challenges in applying the nZEB concept.